Analisis Timesheet Tracking Pada Monitoring Pelaksanaan Proyek Berbasis Odoo Framework - Ilyas Abdurachman (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Consulting Firm is a consulting, training and research institution specializing in improving productivity and quality through human resources. To ensure the project is effective and efficient, the Company assigns a Project Management Officer (PMO) to ensure that the project runs well and smoothly. Therefore it is necessary to do an analysis to determine the effectiveness and efficiency of project implementers so that recommendations for the right team to run the project can be obtained. From the results of the performance analysis using the Elbow Method, from the number of clusters of 10, the most elbow point is obtained at C4 so that the number of clusters suitable for this study is 4 clusters. By testing the K-Means 4 cluster algorithm, it was found that C3 was the best cluster with an average project implementation time of 2.7 hours, a total of 1,530 completed project activities and an average cost of Rp. 365,536. The type of project that was most completed based on clustering was the Consulting project and the most project executors were Consultants. In this way the PMO gets references from the cluster in determining the next project team by selecting the right team so that the implementation is on time and according to plan. So that projects can be more effective and efficient based on the dimensions of cost, quality and time